Level of physical activity, stress and health of bank clerks - M.S. Viana; A. Andrade; A.R. Back; D.I.C. Vasconcellos (Desafio Singular, 2010)
The purpose of this study was to investigate the relationship among level of physical activity, stress and health in male and female bank clerks. Two hundred eighty three bank clerks answered the Questionnaire of Habitual Physical Activities (Pate et al., 1995), the Perceived Stress Scale (Cohen, Karmack, & Mermelsteinm, 1983), and two scales of self-evaluated health (Andrade, 2001). More active bank clerks showed themselves as less stressed (F = 4.87, p = .008), significant results only for women (F = 4.11, p = .019). More active bank clerks also perceived themselves as healthier (p = .000, gamma = .56) and fell ill less frequently (p = .02, gamma = −.34), significant results only for men (p = .001, gamma = .60 e p = .033, gamma = −.33, respectively). Bank clerks with better perceived health showed significantly lower stress (F = 13.45, p = .000), significant results for both men (F = 9.75, p = .000) and women (F = 7.88, p = .000), as well as those getting sick less frequently (F = 5.40, p = .001), significant results only for women (F = 4.60, p = .004). Findings indicated a relationship among all the variables investigated and differing relationships for men and women.